Trends in Problem-Based Learning (PBL) Models to Improve Science Process Skills in Students' Science Learning (2015-2024): A Systematic Review - Cahyani, Novia Intan; Doyan, Aris; Purwoko, Agus Abhi; Sani, Yunita Arian (Balai Publikasi Indonesia, 2025)
Intelligence ecological must owned by each humans to be able to interact with Good together nature, science process skills can improved through various method. PBL is one of the learning models based on problems that have been tested as one of the to increase science process skills through settlement problem. Research This is analysis literature data about study science process skills. The data used in study This obtained from Google Scholar indexed documents from 2020-2024 using Publish or Perish and Dimension.ai. Procedure study use PRISMA guidelines. Data identified and analyzed is type publications, sources publication, and title study about the PBL model for increase science process skills in lots of science learning quoted. The data analysis method uses analysis assisted bibliometrics​ with device VOS viewer software. Research results Analysis show that trend PBL model research for increase science process skills in Google Scholar indexed science learning from 2020 to 2024 experienced​ fluctuating increase. However, in 2024 it will happen decline trend study about it. There are many document in form articles, proceedings, chapters, preprints, and edited books that discuss study about the PBL model for increase science process skill